2006
DOI: 10.1128/iai.01237-05
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal Neuraminidases A and B Both Have Essential Roles during Infection of the Respiratory Tract and Sepsis

Abstract: We examined the role of the neuraminidases NanA and NanB in colonization and infection in the upper and lower respiratory tract by Streptococcus pneumoniae, as well as the role of these neuraminidases in the onset and development of septicemia following both intranasal and intravenous infection. We demonstrated for the first time using outbred MF1 mouse models of infection that both NanA and NanB were essential for the successful colonization and infection of the upper and lower respiratory tract, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
188
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 173 publications
(200 citation statements)
references
References 29 publications
9
188
1
2
Order By: Relevance
“…For example, NanA remodels mucosal cell surface glycoproteins to promote bacterial colonization of the upper respiratory tract (11,12) and contributes to pulmonary inflammation along with the development of SPN pneumonia (13,14). However, the host has adapted to counteract the pathological effects of this SPN virulence factor by the clearance from blood circulation of host factors bearing AMR ligands that have been unmasked by NanA desialylation.…”
mentioning
confidence: 99%
“…For example, NanA remodels mucosal cell surface glycoproteins to promote bacterial colonization of the upper respiratory tract (11,12) and contributes to pulmonary inflammation along with the development of SPN pneumonia (13,14). However, the host has adapted to counteract the pathological effects of this SPN virulence factor by the clearance from blood circulation of host factors bearing AMR ligands that have been unmasked by NanA desialylation.…”
mentioning
confidence: 99%
“…Previous studies reported a substantially reduced bacterial burden in the lungs of mice infected intranasally with nan A and/or nan B gene deletion mutant strains and improved host survival [39,40,68]. NanA was shown to contribute to nasopharyngeal colonisation [41,43,6870].…”
Section: Discussionmentioning
confidence: 99%
“…Both enzymes were demonstrated to be involved in colonization and infection of the upper and lower murine respiratory tract [39,40], although no defect in murine colonization was reported by others using a pneumococcal strain deficient in nanA, bgaA and strH [28]. Additional roles of NanA during persistance in the chinchilla middle ear infection model were shown [4143].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. pneumoniae, for example, uses neuraminidase to break down the glycoprotein barrier to cellular entry. 3 However, by chopping off sialic acid, the bacterial enzyme actually helps the Ashwell receptor to recognize compromised proteins and thus, paradoxically, helps it clear these defective proteins from circulation.…”
mentioning
confidence: 99%